Titanium carbide-decorated graphite felt as high performance negative electrode in vanadium redox flow batteries - Ghimire, Purna Chandra (2020)
This paper presents a novel method for preparing binder-free, uniformly distributed titanium carbide (TiC) nanoparticles on graphite felt (GF) surfaces for use as negative electrode in an all vanadium redox flow battery (VRFB). TiO2 particles were grown on the surface of the GF using hydrothermal synthesis and were subsequently converted to TiC by way of a carbothermal reaction. Cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and VRFB single cell tests unequivocally confirm the catalytic effect of TiC towards the negative redox couple V2+/V3+. A VRFB employing a TiC-decorated electrode in the negative half-cell exhibited a 13% gain in energy efficiency (EE) at a current density of 100 mA cm−2, compared to reference cells assembled solely with pristine graphite felts. Moreover, VRFB cells employing the modified electrode show excellent stability with high capacity retention over repetitive cycling. These results suggest that TiC nanoparticles supported on carbon fibres constitute a high performance negative electrode for VRFBs.